1997
DOI: 10.1200/jco.1997.15.4.1318
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection with dexrazoxane for doxorubicin-containing therapy in advanced breast cancer.

Abstract: DZR had a significant cardioprotective effect as measured by noninvasive testing and clinical CHF. One of the two studies (088001) showed a lower response rate with DZR, but time to progression and survival were not significantly different. DZR is the first agent shown to reduce cardiotoxicity from doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
279
0
11

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 569 publications
(309 citation statements)
references
References 24 publications
7
279
0
11
Order By: Relevance
“…every 3 weeks and were randomized to receive either DZR (500 mg/m 2 or 1000 mg/m 2 ) or placebo. 2,3 There was no maximum dose for doxorubicin, and no patients had received anthracyclines previously. The protocols for Studies 088001 and 088006 were identical.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…every 3 weeks and were randomized to receive either DZR (500 mg/m 2 or 1000 mg/m 2 ) or placebo. 2,3 There was no maximum dose for doxorubicin, and no patients had received anthracyclines previously. The protocols for Studies 088001 and 088006 were identical.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…2,3 The results of those studies indicated that DZR provided significant cardioprotection, 2 even if treatment started after a cumulative doxorubicin dose of 300 mg/m 2 had been administered. 3 The 2.2% incidence of doxorubicin-related CHF reported by Von Hoff et al 1 may not have been an accurate reflection of the true incidence of this adverse event.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cell fraction (sub-G1) in PI-stained cells was measured by flow cytometry as described previously (Swain et al, 1997;Suresh et al, 2003). In brief, after trypsinisation the cells were resuspended in PI staining solution (50 mM ml À1 PI, 0.1% sodium citrate, 0.1% TritonX-100, 0.1 mg ml À1 Rnase in PBS).…”
Section: Flow Cytometric Analysis Of Pi-stained Cellsmentioning
confidence: 99%
“…Various strategies have been developed to protect against DOX-induced cardiotoxic effects. The majority of these studies concern either metal ion chelators or antioxidants that yielded moderate protective effects (Swain et al, 1997;Kotamraju et al, 2000;Liu et al, 2002;Yamanaka et al, 2003;Oliveira et al, 2004).…”
mentioning
confidence: 99%